Ocular Phenotype of Relaxin Gene Knockout (Rln-/-) Mice. (2nd October 2020) - Hampel, Ulrike; Chinnery, Holly R.; Garreis, Fabian; Paulsen, Friedrich; de Iongh, Robb; Bui, Bang V.; Nguyen, Christine; Parry, Laura; Huei Leo, Chen
ABSTRACT: Purpose : To test if relaxin deficiency affects ocular structure and function we investigated expression of relaxin ( Rln ) and RXFP receptors ( Rxfp1, Rxfp2 ), and compared ocular phenotypes in relaxin gene knockout ( Rln −/− ) and wild type ( Rln +/+ ) mice. Materials and Methods : Rln, Rxfp1 and Rxfp2 mRNA expression was detected in ocular tissues of Rln+/+ mice using RT-PCR. The eyes of 11 Rln −/− and 5 Rln +/+ male mice were investigated. Corneal and retinal thickness was assessed using optical coherence tomography. Intraocular pressure was measured using a rebound tonometer. Retinal, choroidal and sclera morphology and thickness were evaluated histologically. Eyes were collected and fixed for immunofluorescence staining or used for RNA extraction to evaluate mRNA expression using real-time PCR. Results : Rln mRNA was expressed only in the retina, whereas Rxfp1 transcripts were detected in the retina, cornea and sclera/choroid. Rxfp2 was only present in the cornea. None of these genes were expressed in the lacrimal gland, eyelid or lens. Intraocular pressure was higher and central cornea of Rln −/− mice was significantly thicker and had significantly larger endothelial cells and a lower endothelial cell density than Rln +/+ mice. Immunohistochemistry demonstrated no significant difference in AQP3 and AQP5 staining in the cornea or other regions between wildtype and Rln −/− mice. mRNA expression of Aqp4 was significantly higher in Rln −/− than in Rln +/+ corneas, whereas Col1a2, Mmp9, Timp1 and Timp2 were significantly decreased. Expression of Aqp1, Aqp4, Aqp5, Vim and Tjp1 was significantly decreased in Rln −/− compared to Rln +/+ uvea. No significant differences in these genes were detected in the retina. Retinal, choroidal and scleral thicknesses were not different and morphology appeared normal. Conclusion : The findings indicate that loss of Rln affects expression of several genes in the uvea and cornea and results in thicker corneas with altered endothelial cells. Many of the gene changes suggest alterations in extracellular matrix and fluid transport between cells.